Socialization on the Use of Medicinal Plants in Kuripan Village, Kuripan District, West Lombok Regency - Sari, Dwi Melinda; Handayani, Eka Wuri; Miyarso, Chondrosuro (Prosiding University Research Colloquium, 2022)
Traditional medicine is ingredients or ingredients derived from plants, animals, minerals, preparations of extracts (galenic), or mixtures of these materials, which have been used for generations for treatment based on experience. The use of traditional medicine in Indonesia has long been known. However, knowledge about what plants can be used, the dose, side effects of drugs that may appear, and how to process medicinal plants that will be used correctly are not widely known by the public. The wrong dose and the wrong way of processing will result in the therapeutic objectives with the plants used being unable to be achieved. The counseling activity was carried out in Kuripan village, Kuripan sub-district, West Lombok district, which aims to provide information on how to use traditional medicinal plants commonly consumed by the community. The method used is Focus Group Discussing (FGD) with media power pints and leaflets. The results of the counseling showed that the community had increased knowledge as evidenced by the increase in the posttest score with an average value of 84. After this service was carried out, it could be seen that the community had known and applied good traditional medicine processing methods. It is hoped that with this treatment goals can be achieved maximally and with minimal side effects so that it has an impact on improving the quality of public health.